(untitled) (Medical Forum Monthly, 2024)
Objectives: This study was conducted to determine the frequency of obstetric hysterectomy, morbidity and mortality associated with it. Study Design: Descriptive study Place and Duration of Study: This study was conducted at civil hospital Bahawalpur including the patients attending Gynae emergency, OPD and Indoor of Civil Hospital Bahawalpur from January 2016 to June 2016. Materials and Methods: All emergency obstetric hysterectomies done for primary or secondary PPH were included in the study. Hysterectomies done for early pregnancy complications, like perforated uterus due to induced abortion, were excluded. Data regarding frequency of EOH, maternal age, parity, booking status, indications for hysterectomy, type of hysterectomy done and its complications, was collected by pre-designed Performa containing demographic data, risk factors, indications; complications, and SPSS V.21 used for analysis. Results: Most of the women were in age group 26-30 years of age 11(68.75%) & mostly were Multipara 55%. Atonic Uterus 6(37.5%) was the major indication for obstetrical hysterectomy followed by Adherent placenta 3(18.75%), Ruptured Uterus 2(12.5%), Septic Uterus 2(12.5%),and Uterine Inversion 1(6.25%). Bladder Rapture 5(31.25%) was the major intra or post op complication followed by fever, infection 18.75% and repeat laparotomy 12.5%.DIC complication was 2(12.5%).Mortality was seen in 6.25% cases. Conclusions: The incidence of obstetrical hysterectomy in our area is relatively high and may be due to a large number of cases handed over from rural areas. These patients have risk factors such as high parity, maternity leave and family planning services.